2020
DOI: 10.7717/peerj.9588
|View full text |Cite
|
Sign up to set email alerts
|

Identification of viruses infecting six plum cultivars in Korea by RNA-sequencing

Abstract: Background Plums are a kind of stone fruit, a category that includes peaches, cherries, apricots, and almonds. In Korea, Japanese plum trees are usually cultivated as they best suit the climate. To date, there have been few studies in Korea on viruses infecting plum trees compared to those infecting peach trees. Methods To identify viruses and viroids infecting plum trees, we collected leaf samples from six different plum cultivars and subjected them to RNA-sequencing (RNA-seq). Six different plum transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Similarly, in single peach trees multi-viral infection of up to six viruses and viroids was detected ( Jo et al, 2018 ). A multiplicity of viral infections was also shown in metagenome samples from single plum trees ( Jo et al, 2020 ). A possible explanation for the single viral infection in the maple tree could be the age of the tree; it was very young (approx.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, in single peach trees multi-viral infection of up to six viruses and viroids was detected ( Jo et al, 2018 ). A multiplicity of viral infections was also shown in metagenome samples from single plum trees ( Jo et al, 2020 ). A possible explanation for the single viral infection in the maple tree could be the age of the tree; it was very young (approx.…”
Section: Discussionmentioning
confidence: 91%
“…However, BLAST results for such short sequences sometimes lead to misidentification, even though partial sequences are derived from a single viral sequence (Jo et al, 2017). Although several studies have identified novel viruses of stone fruits using NGS (Jo et al, 2018a(Jo et al, , 2020, no novel viruses or viroids of pear was identified in the present study. Nevertheless, the obtained information is useful for documenting the virosphere diversity of pear trees.…”
Section: Discussionmentioning
confidence: 66%
“…Detection of viruses using classic methods, such as ELISA and RT-PCR, is often limited in terms of identifying novel virus species ( Jeong et al, 2014 ; Ji et al, 2013 ). In addition to increasing the rate of virus discovery, NGS has been used to detect viruses and viroids in various fruit trees, including citrus, and peach ( Jo et al, 2018b , 2020 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, DNA and RNA shotgun sequencing can reveal not only microbial communities but also all living organisms within the samples [25,26]. Viruses do not possess any conserved sequences like bacteria and fungi, therefore, RNA sequencing is frequently used to identify viruses infecting plants [27,28]. Although NGS followed by bioinformatic analyses can reveal the microbial community composition in detail, it might be difficult to distinguish viable microorganisms from NGS data.…”
Section: Introductionmentioning
confidence: 99%